GA-PSO Based Clustering Algorithm For Multi View Data: A Survey - Patel, Amitosh; Mudgil, Shuchita (International Journal of Computer Sciences and Engineering, 2025)
Data mining an non-trivial extraction of novel, implicit, and actionable knowledge from large data sets is an evolving technology which is a direct result of the increasing use of computer databases in order to store and retrieve information effectively. This paper gives an idea of optimization algorithm by which the efficient result can be fetched. Optimization is a dire need for a huge amount of data processing. So that optimization is a challenging issue in data mining. It seems to be that there are many different approaches has been proposed by authors in order to optimize the results. Partial swam optimization and genetic algorithms are some sort of approach which can be used for optimization.